2009
DOI: 10.1002/ejic.200900221
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric and Dimeric Copper(II) Complexes of a Pyrrole‐Containing Tridentate Schiff‐Base Ligand

Abstract: Three copper(II) complexes of (L1)–, [CuL1Cl] (1), [CuL1Br]n (2) and [Cu2(L1)2(μ1,3‐NCS)2] (3), and two copper(II) complexes of HL1, [Cu(HL1)X2] (X = Cl–, 4; X = Br–, 5), have been prepared and characterised [where HL1 is the Schiff‐base ligand derived from pyrrole‐2‐carbaldehyde and 2‐aminomethylpyridine]. The removal of a chloride ion and deprotonation of [Cu(HL1)Cl2] (4) to form [CuL1Cl] (1) worked well. However, attempts to protonate [CuL1Cl] with HCl to re‐form [Cu(HL1)Cl2] were not successful. X‐ray stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In the previous work with a Zn­(SNS) 2 hydroboration precatalyst, we also showed that the basic amido group binds strongly to the Bpin group, reducing the ligand’s ability to coordinate the metal . As a result, we turned to the less basic pyrrolyl group in L 2 . , …”
Section: Resultsmentioning
confidence: 92%
“…In the previous work with a Zn­(SNS) 2 hydroboration precatalyst, we also showed that the basic amido group binds strongly to the Bpin group, reducing the ligand’s ability to coordinate the metal . As a result, we turned to the less basic pyrrolyl group in L 2 . , …”
Section: Resultsmentioning
confidence: 92%
“…The basal coordination sites are occupied by the three donor atoms of the Schiff-base ligand and the bromine atom Br(1) for 1 or one nitrogen atom [N(3) or N(8)] of the azide ligand for 2, while the apical position is occupied by the bromine atom [Br(1A)] for 1 or one nitrogen atom [N (10) or N(5A)] of the azide ligand of the next repeating unit. The apical Cu-Br(1A) (1) or Cu-N(azide) [Cu(1)-N(10), Cu(2)-N(5A)] (2) bond is significantly longer than the corresponding basal Cu-Br(1) (1) or Cu-N [Cu(1)-N(3), Cu(2)-N( 8)] (2) bond (Tables 2 and 3), a feature which appears frequently in square-pyramidal copper(II) complexes [23][24][25][26] . The copper atom is located 0.1682(15) Å for 1 or 0.1063(29) and 0.0828 (29) for 2 out of the basal plane towards the apical ligand.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of 1 – 5 is shown in Scheme . The tridentate pyrrole ligand C 4 H 3 NH(2‐CH=NCH 2 Py) was synthesized according to a method reported in the literature 7d. The reaction between 1 equiv.…”
Section: Results and Discussion Synthesis And Characterization Of 1–5mentioning
confidence: 99%